Interaction of potential and effective entrepreneurial capabilities in adolescents: Modeling youth entrepreneurship structure using structural equation modeling - Lilia Campo-Ternera; Paola Amar-Sepúlveda; Enohemit Olivero-Vega (Journal of Innovation and Entrepreneurship, 2022)
This article emphasizes entrepreneurial skills in adolescents, in order to determine the relationship between entrepreneurial skills (dependent variable) and the key factors for their development: personal, social, and educational (independent variables). It has an empirical‒analytical design which is explanatory in nature. After the design, validation, and application of the evaluation instrument, the estimation was carried out using Structural Equation Modeling (SEM). The results show great impact of potential entrepreneurial capacity on effective entrepreneurial capacity, determined by the direct effect of personal traits and life skills, the family as a moderating element, as well as the mediating role of entrepreneurship training processes. The complex nature of entrepreneurship is highlighted, which is influenced by multiple factors as possible boosters for the success of entrepreneurial initiatives.
Keywords: 650; Entrepreneurial skills; Entrepreneurship; Entrepreneurship training; Personal attributes; Social skills